Peranan Perempuan Tani dalam Meningkatkan Ekonomi Keluarga di Kelurahan Bonto Langkasa Kecamatan Bissappu Kabupaten Bantaeng - Risal, Risal; Agustang, Andi; Syukur, Muhammad (Phinisi Integration Review, 2021)
This study aims to determine: (1) the contribution of women farmers in empowering the family economy in Bonto Langkasa Village, Bissappu District, Bantaeng Regency; (2) Allocation of time distribution to women's farming families in Bonto Langkasa Village, Bissappu District, Bantaeng Regency; (3) Decision making on the families of women farmers in Bonto Langkasa Village, Bissappu District, Bantaeng Regency. This research uses qualitative research with a descriptive approach. Based on the source, the types of data used are primary and secondary data. Primary data obtained through the t-interview method, the informants in this study were selected based on respondents who have the capability and credibility in accordance with the problems in the study, where they can provide very accurate information as well as documentation and observations. While secondary data is data obtained from various literatures such as books, laws and other related sources. Processing and presentation of data is done descriptively. The results showed that: (1) The contribution of women farmers in empowering the family economy in the Bonto Langkasa Village, Bissappu District, Bantaeng Regency, besides acting as housewives who did all household chores, they also contributed by working to earn a living such as by farming for increase their economic income in order to achieve prosperity. (2) Despite the workload faced by women as farmers and housewives, and with all the limited time they have, women farmers still have responsibilities related to the household (children and husband). (3) Decision-making on the families of women farmers in Bonto Langkasa Village, Bissappu District, Bantaeng Regency, husband and wife are balanced in decision making